Bacterial Spectrum and Antibiotic Susceptibility Patterns in Nosocomial Pneumonia in the Intensive Care Unit - Khan, Mumtaz Ahmad; khan, Mumtaz Ali; Ahmed, Khawaja Ashfaq (International Journal of Pathology, 2018)
Background: Nosocomial pneumonia is the most common infection acquired in the hospital with the highest prevalence in intensive care units (ICUs). Antimicrobial resistance is an important factor in predicting outcomes and resources used in ICUs. Globally ICUs are facing the emergence and spread of antibiotic-resistant pathogens, and for some pathogens there are few therapeutic options available. Objective: To evaluate the bacterial spectrum from patients with nosocomial pneumonia in the intensive care unit of a secondary care hospital in Saudi Arabia, and their antibiotic susceptibility patternsMethods: This prospective, descriptive study was carried out at the Department of Microbiology, King Abdullah Hospital in Bisha from June 2011 to May 2012. Lower respiratory tract samples were obtained from suspected cases of nosocomial pneumonia in the ICU. The specimens were cultured on appropriate media. The identification of bacteria and susceptibility testing were done by using BD PhoenixTM Automated Microbiology system. In vitro antibiotic susceptibility patterns were analyzed using WHONET software.Results: A total of 301 clinical isolates were analyzed. The frequencies of Gram-positive and Gram-negative bacteria were 16% and 84% respectively. Among Gram-positive bacteria, Methicillin-sensitive Staphylococcus aureus (MSSA) and Methicillin-resistant Staphaureus (MRSA) were the leading pathogens, while, Acinetobacter, Klebsiella and Pseudomonas species were the most common Gram-negative isolates. 79% isolates of Acinetobacter species were resistant to carbapenem, while 3 were resistant to all the antibiotics tested including colistin and were declared as pan-drug resistant Acinetobacter. Extended-spectrum beta-lactamase-producing K. pneumoniae accounted for 28% of all Klebsiella species isolated and24% of Pseudomonas species were resistant to ceftazidime.Conclusion: The Gram-negative bacteria remained more prevalent in ICU patients with nosocomial pneumonia. The reduced antibiotic susceptibility among Gram-negative bacteria alerts us that more effective strategies are needed to control the spread of antibiotic resistant organisms in critical patient areas.